PENGARUH FREE CASH FLOW, FINANCIAL DISTRESS, DAN INVESTMENT OPPORTUNITY SET TERHADAP MANAJEMEN LABA: STUDI PADA PERUSAHAAN INFRASTRUKTUR, TRANSPORTASI, DAN LOGISTIK - Putri, Sanniyah Alya; Andriani, Wiwik; Fontanella, Amy; Zahara, Zahara (Jurnal Riset Akuntansi Politala, 2025)
This study aims to determine and analyse how free cash flow, financial distress, and investment opportunity set affect earnings management. This study uses the years 2018-2022 with this research sample includes 28 infrastructure, transportation, and logistics companies listed on the Indonesia Stock Exchange. Purposive sampling is the sampling method used. Coefficient similarity test, descriptive statistical test, classical assumption test, and multiple linear regression analysis are the test procedures performed. According to the results of this study, free cash flow has no effect on earnings management, financial distress has a significant negative effect on earnings management, and investment opportunity set has a significant positive effect on earnings management.